Carbon‐Coated Li3VO4 Spheres as Constituents of an Advanced Anode Material for High‐Rate Long‐Life Lithium‐Ion Batteries. Issue 33 (22nd June 2017) - Shen, Laifa; Chen, Shuangqiang; Maier, Joachim; Yu, Yan
Abstract : Lithium‐ion batteries are receiving considerable attention for large‐scale energy‐storage systems. However, to date the current cathode/anode system cannot satisfy safety, cost, and performance requirements for such applications. Here, a lithium‐ion full battery based on the combination of a Li3 VO4 anode with a LiNi0.5 Mn1.5 O4 cathode is reported, which displays a better performance than existing systems. Carbon‐coated Li3 VO4 spheres comprising nanoscale carbon‐coating primary particles are synthesized by a morphology‐inheritance route. The observed high capacity combined with excellent sample stability and high rate capability of carbon‐coated Li3 VO4 spheres is superior to other insertion anode materials. A high‐performance full lithium‐ion battery is fabricated by using the carbon‐coated Li3 VO4 spheres as the anode and LiNi0.5 Mn1.5 O4 spheres as the cathode; such a cell shows an estimated practical energy density of 205 W h kg −1 with greatly improved properties such as pronounced long‐term cyclability, and rapid charge and discharge. Abstract : Advanced carbon‐coated LVO (LVO⊂C) sub‐micrometer spheres comprising nanoscale carbon‐coating primary particles are synthesized by a morphology‐inheritance route. When combined with a LiNi0.5 Mn1.5 O4 cathode, the rationally designed full cell demonstrates an estimated energy density of 205 W h kg −1, high‐power performances up to 20 C, and pronounced long‐term cyclability.